Fuzzy clustering based pseudo-swept volume decomposition for hexahedral meshing. (March 2018) - Wu, Haiyan; Gao, Shuming; Wang, Rui; Chen, Jinming
Abstract: To facilitate automatic and high-quality hexahedral meshing of complex 3D product models, a pseudo-swept volume decomposition approach is proposed in this paper, which can automatically decompose a complex solid model into a set of sub-volumes, including all of the pseudo-swept volumes. First, the sweep directions and faces of potential pseudo-swept volumes are recognized using a fuzzy clustering algorithm. Then, all of the interacting potential pseudo-swept volumes are separated by the recursive construction of optimized cutting face sets, with the solid model decomposed at the same time. In particular, the pseudo-swept volumes resulting from our approach are suitable for high-quality hexahedral meshing. The efficiency and effectiveness of this approach are demonstrated by several experimental results. Highlights: We propose an automatic and optimized pseudo-swept volume decomposition approach. Potential pseudo-swept volumes are recognized using a fuzzy clustering algorithm. Interacting potential pseudo-swept volumes are separated by the construction of optimized cutting face sets. The decomposition results are suitable for high quality hexahedral meshing.